Investigations of thermal plasma of electric arc discharge between composite Ag–C electrodes - Veklich, A.N.; Fesenko, S.O.; Kleshich, M.M.; Boretskij, V.F.; Cressault, Y.; Teulet, Ph. (Вопросы атомной науки и техники, 2016)
The complex investigation of the arc discharge plasma between composite Ag–C electrodes in the range of
3.5 A…30 A currents was carried out. Plasma temperature in assumption of local thermodynamic equilibrium was
obtained by optical emission spectroscopy. Electron densities were obtained from half-width of Ag I 466.8 nm
spectral line in the assumption of dominating quadratic Stark effect emitted by plasma at arc current 30 A. Electrical
conductivity and electron density in arc discharge plasma at current 3.5 A were obtained by solution of the energy
balance equation. The results of investigations of plasma arc discharge between Ag–C electrodes were compared
with parameters of discharge plasma between C–Cu electrodes at arc current 3.5 A Выполнено комплексное исследование плазмы электродугового разряда между композитными Ag–C
электродами в диапазоне токов 3,5…30 A. Методом оптической эмиссионной спектроскопии определена
температура плазмы в предположении локального термодинамического равновесия. Электронная
концентрация плазмы электродугового разряда силой тока 30 A определена по уширению спектральной
линии Ag I 466,8 нм. Электропроводность и электронная концентрация плазмы дугового разряда силой тока
3,5 A определены путем решения уравнения энергетического баланса. Результаты исследований плазмы
дугового разряда силой тока 3,5 А между Ag–C электродами сравнивались с параметрами плазмы разряда
между C–Cu электродами. Виконано комплексне дослідження плазми електродугового розряду між композитними Ag–C електро-
дами в діапазоні струмів 3,5…30 A. Методом оптичної емісійної спектроскопії визначено температуру плаз-
ми у припущенні локальної термодинамічної рівноваги. Електронна концентрація плазми електродугового
розряду силою струму 30 A визначена із ширини спектральної лінії Ag I 466,8 нм. Електропровідність та
електронна концентрація плазми дугового розряду силою струму 3,5 A визначені шляхом розв’язку рівняння
енергетичного балансу. Результати досліджень плазми дугового розряду силою струму 3,5 А між
Ag–C електродами порівнювались з параметрами плазми розряду між C–Cu електродами.